35 To pan-scan or not to pan-scan? Further analysis of the tarn database 2012–2017. Issue 12 (23rd November 2017) - Hunt, Paul; Lecky, Fiona; Bouamra, Omar
Abstract : Background: A 'whole body' or 'pan-scan' computed tomography (CT) imaging approach is now becoming the standard of care during the early management of adult patients with suspected severe blunt multitrauma. A number of studies have variously reported a mortality benefit or no benefit from a pan-scan approach compared to that of carrying out body region-focused CT and/or plain radiographs or a mixture of imaging modalities. However, unanswered questions still remain due to the significant heterogeneity in practice between institutions, and the limitations of published studies. The potential risk for harm from ionising radiation or intravenous contrast-induced nephropathy is still a concern, especially where mortality benefit from an unselective pan-scan approach is yet to be definitively proven. We present the results of our latest analysis of the Trauma Audit and Research Network (TARN) database; updated to take into account the establishment of the regional trauma network system and focusing on the Major Trauma Centre's (MTC's). Methods: We analysed retrospective, multicentre data of severe blunt multitrauma (ISS >15) direct MTC admissions aged >15 years recorded in the UK TARN database from 2012–2017 to compare survival at 30 days between two groups of patients: (1) those undergoing pan-scan, and (2) those in receipt of a focussed/non-pan-scan approach as part of their initial management within the first 4 hours in the Emergency Department (ED). The final dataset included 44 407 cases. Results: 15 645 (35.2%) of 44 407 cases underwent pan-scan from the ED. The median ISS for the pan-scan group was 18 (IQR 10–29) compared to 16 (IQR 9–25) for the non-pan-scan group. The calculated crude mortality rate for the pan-scan group was 11.2% compared to 10.6% in the focussed CT group (p=0.0673). Patient characteristics are shown in table 1 . Propensity scoring (PS) was used to create a balance in patient characteristics between the two groups and various statistical models derived to analyse the effect of imaging type (exposure factor) on outcome (mortality at 30 days) as shown in table 2 . The results show that pan-scan has an adverse effect on outcome in all of the models, although not statistically significant in all except Model 2 (adjustment based only on stratified PS). Conclusion: The results of our investigation demonstrate that there is no risk adjusted mortality benefit observed from current practice in MTCs in England and Wales. Key issues remain to be addressed such as pan-scan selection criteria and the significant heterogeneity observed in practice across institutions.